A Pedra, a Informante e o Etnógrafo: ou sobre quando as expectativas das nossas idas a campo não se realizam - Braga, Antônio (Instituto de Estudos da Religião, 2015)
Abstract The objective of this paper is to reflect about the researcher-researched relationship during the practice of the ethnographic research. The purpose is to problematize issues such as the relationship of intersubjectivity between researcher and native, the native agency during the fieldwork and the experience of “being affected” (Favret-Saada 2005), which can be experienced by the researcher in the course of the fieldwork. The starting point is an experience of the fieldwork conducted during one of the pilgrimage rituals in Juazeiro do Norte, Ceará, Brazil, known as “visit to the Horto”. As reported in the text and explained at the title, this fact is around me (the ethnographer), one of my key informants and a stone.

Resumo O objetivo deste artigo é refletir sobre a relação pesquisador-pesquisado durante a prática da pesquisa etnográfica. Busca-se problematizar questões tais como as relações de intersubjetividade entre pesquisador e nativo, a agência do nativo durante a pesquisa de campo e a experiência de “ser afetado” (Favret-Saada 2005), que é passível de ser experimentada pelo pesquisador no decorrer do trabalho de campo. O ponto de partida da reflexão é um fato ocorrido comigo durante pesquisa de campo sobre um dos rituais das romarias de Juazeiro do Norte, Ceará, Brasil, conhecido como “visita ao Horto”. Como é relatado no texto e já explicitado no título, o fato em questão envolveu a mim (etnógrafo), umas das minhas principais informantes e uma pedra.
The Stone, The Informant and the Ethnographer: about when the expectations of our fieldwork are not realized
Keywords: fieldwork; ethnography; pilgrimage; popular devotion; trabalho de campo; etnografia; romarias; devoção popular